2019
DOI: 10.1038/s42003-018-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

Initial hydraulic failure followed by late-stage carbon starvation leads to drought-induced death in the tree Trema orientalis

Abstract: Drought-induced tree death has become a serious problem in global forest ecosystems. Two nonexclusive hypotheses, hydraulic failure and carbon starvation, have been proposed to explain tree die-offs. To clarify the mechanisms, we investigated the physiological processes of drought-induced tree death in saplings with contrasting Huber values (sapwood area/total leaf area). First, hydraulic failure and reduced respiration were found in the initial process of tree decline, and in the last stage carbon starvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 50 publications
2
39
0
1
Order By: Relevance
“…This may be a result of the seasonal variation of gas exchange in C. japonica: [47] reported that whole plant evaporation increased significantly from March to April, possibly because this species requires a lot of water for gas exchange (i.e., photosynthesis) during early spring. High water demand during a dry period decreases the plant's water potential; the water deficit further causes dehydration and cavitation in leaf and stem, resulting in cell turgor [48][49][50], which inhibits photosynthesis and metabolic activity [51][52][53]. The response of C. japonica stem growth to water deficit was investigated previously using irrigation experiments [54,55].…”
Section: Climate Change Sensitivitymentioning
confidence: 99%
“…This may be a result of the seasonal variation of gas exchange in C. japonica: [47] reported that whole plant evaporation increased significantly from March to April, possibly because this species requires a lot of water for gas exchange (i.e., photosynthesis) during early spring. High water demand during a dry period decreases the plant's water potential; the water deficit further causes dehydration and cavitation in leaf and stem, resulting in cell turgor [48][49][50], which inhibits photosynthesis and metabolic activity [51][52][53]. The response of C. japonica stem growth to water deficit was investigated previously using irrigation experiments [54,55].…”
Section: Climate Change Sensitivitymentioning
confidence: 99%
“…This may be due to the mobilization of photosynthate was constrained by phloem transport caused by summer drought [58][59][60][61]. In order to better elucidate the causes of low NSCs in roots, the future studies should give more attention on the capacity of phloem transport by using carbon isotope technique [62,63]. In addition to this, the influence of different development stage on NSC demand cannot be excluded.…”
Section: Nsc Variationmentioning
confidence: 99%
“…Our data suggest that the decline of some P. nigra individuals arise as a consequence of xylem embolism triggered by drought stress, coupled to impending carbon starvation (Kono et al ., 2019). Considering that the woodland under study results from reforestation, we hypothesized that the differential drought impact on individuals could be linked to different origins of seeds/seedlings used, also taking into account that P. nigra displays high genetic distance between populations (Thiel et al ., 2012) and considering that provenance-based differences in xylem vulnerability have been reported for different Pinus species.…”
Section: Discussionmentioning
confidence: 78%